Tun Dr. Mahathir and the Notion of ‘Bangsa Malaysia’ (Journal of International Studies, 2020)
The question of nation-building has always been a central issue in Malaysian politics. Despite its relatively stable politics and constant economic development, the project of nation-building remained a basic national agenda yet to be fully resolved. The notion of 'Bangsa Malaysia' that was officially introduced by Dr Mahathir in 1991, as part of the package in his Vision 2020 project, was aimed to resolve the 'unfinished business' in the project of nation-building. Vision 2020 is a grand national project span for a period of one generation designed to turn Malaysia into a fully developed state in its 'own mould' by the year 2020. This paper attempts to examine the notion of 'Bangsa Malaysia' as it is envisages by Tun Dr. Mahathir Mohamad. The paper argues that since there exist a potent interplay between the forces of ethnicity and nationalism that has resulted in the creation of a competing notion of nation-of-intent among the various ethnic groups in Malaysia, the idea of 'Bangsa Malaysia, therefore,' could be seen as an attempt to mediate this contestation. The question is, does the meaning of the concept clear to all Malaysians? To what extent would the notion of 'Bangsa Malaysia' be able to reconcile the competing ethnic ideologies of a nation? Can it be a successful venture, or perhaps add to further complicates the politics of nation-building in Malaysia? It is hoped that this humble contribution would be able to highlight some of the important ideas of Tun Dr. Mahathir's thoughts in regard to the question of ethnic relations and nation-building in Malaysia.